Harga Diri dan Adiksi Internet: Tinjauan Meta-Analisis - Wahyu Rahardjo (Faculty of Psychology Universitas Gadjah Mada, 2019)
The aim of this meta-analysis study is to figure out the true correlation between self-esteem and internet addiction. This meta-analysis uses 159 studies from 40 scientific articles from the year of 2005-2018 and involved in 120.825 participants. Correction for the two artifacts studied in this meta-analysis first is sampling error, and the second one is measurement error. The results support the hypothesis and show some similar findings whereas the true correlations from the groups confirm previous researches that self-esteem has a negative correlation to internet addiction. The strongest correlation found in adolescence group followed by men and women, all participant, also students and college students groups. However, these findings show that the internet accommodates individuals with negative self-esteem to build online social relationships and fulfilling their communication and pleasure needs and makes them easier committed to deviant behavior such as internet addiction.